Uma Conexão Didática entre Sistemas de Equações Lineares de ordem 2 e a Sequência de Fibonacci - LARA NICOLETTI SOTOMA (2025)
When analyzing the National Common Curricular Base (BNCC), it is clear that the terms “matrix” or “matrix representation” are not explicitly considered as specific content in the Mathematics area. However, considering the current context, strongly influenced by the use of data and technologies, it becomes clear that the ability to interpret, organize and operate tables of values is fundamental for the education of students. This work aims to discuss a way to teach matrices and determinants through knowledge provided in the BNCC. These are: systems of linear equations of order 2 and numerical sequences. We propose an application to error-correcting linear codes using the Fibonacci sequence. This interdisciplinarity between the mathematical concepts presented in this dissertation contemplates several BNCC skills in a simple and effective way. Keywords: Linear Systems, Matrices, Determinants, Fibonacci Sequence, Linear Codes.